Relationship Between Explosive Strength Capacity of the Knee Muscles and Deceleration Performance in Female Professional Soccer Players - Zhang, Qingshan; Léam, Aurélie; Fouré, Alexandre; Wong, Del P.; Hautier, Christophe A. (Frontiers in Physiology, 2021)
The present study aimed to investigate the relationship between linear deceleration performance and explosive strength capacity of the knee muscles. Fourteen female professional soccer players completed the maximal sprint deceleration tests and knee flexor (KF) and knee extensor (KE) isokinetic concentric (240°.s-1 and 60°.s-1) and eccentric contractions (30°.s-1). Linear deceleration performance was evaluated from horizontal breaking force (FH), power (PH), and impulse (IH) during a maximal linear deceleration. The peak torque (PT) of KF and KE, PT ratio between KF and KE (conventional and functional H/Q ratio), rate of torque development (RTD) for each muscle group, and RTD between KF and KE (RTD H/Q) were extracted from the isokinetic contractions. Pearson’s correlation coefficients revealed that the eccentric (30°.s-1) and concentric (60°.s-1, 240°.s-1) KE peak torque, and the concentric KF peak torque (240°.s-1) were significantly correlated with FH, PH, and IH (-0.75 < r < -0.54). Moreover, a significant correlation was found between KE RTD during eccentric contraction and FH, PH, and IH (-0.63 < r < -0.54). Besides, a significant correlation was observed between RTD H/Q at 60°.s-1 and PH, IH (-0.61 < r < -0.57). No significant relationship was observed between the H/Q ratio, KF RTD and deceleration performance. These main findings indicated the importance of the ability to quickly produce high KE eccentric torque, contributing to braking force production. Meanwhile, RTD H/Q should be assessed for its essential role in knee joint dynamic stability and can be a relevant index to determine deceleration performance.